Majelis Taklim JN Surabaya sebagai Wahana Hijrah (Transformasi) Bagi Jemaah - Dwi Retnani Srinarwati (Universitas Darussalam Gontor, 2022)
In big cities, including in Surabaya, there are many taklim assemblies. This illustrates the great interest of Muslims to perform 'hijrah' and lead to a more religious life. However, there are many religious activities that are no longer carried out in places of worship and are carried out simply. The purpose of this study is to find out the practice of the JN Surabaya taklim assembly as a vehicle for hijrah (transformation) for the congregation. The type of research chosen in this study is a qualitative research with a qualitative-descriptive form of research. The main data collection techniques in this research are in-depth and open interviews and observational participation. The conclusion obtained from this research is that the taklim assembly brings the congregation's hijrah from not having a salafi ideology to a salafi ideology by implementing it in activities and other elements (materials) according to the provisions that must be followed, as salafi indicators. The salafi group, which is based on the Qur'an and the Sunnah, makes life at the time of the Prophet Muhammad sallallaahu 'alaihi wa sallam and his companions the tabi'in and tabi'it tabi'in as a reference.